Ethnography in movement: bounding the field between the compound and the trailer in Riyadh, Saudi Arabia. Issue 2 (2nd January 2017) - Sawaf, Zina
ABSTRACT: Social anthropological research often deploys ethnographies of dwelling, following and immersing. While many of these ethnographic practices are an essential part, and a matter of fact, of simply being there, research in Riyadh requires doing fieldwork and bounding the field differently. Swathes of highways and boulevards, endless tracts of walls, individual villas and low-rise apartment buildings come to the fore and make their anonymizing and atomizing imprint felt on the ethnographer's oft-cherished 'everyday'. They have earned the city titles such as a 'city of walls', a 'city of closed spaces' or even an 'anti-city'. Serendipity and spontaneity feel elusive and out of reach under the disciplining and surveilling arms of the state as well as the conservatism of society. Drawing inspiration from a Bedouin idiom of movement, shadda, this article lays out how I discovered an alternative method of doing fieldwork under such circumstances. I show how movement—that is, moving alongside, across and through the banalities and complexities of everyday life—is an indispensable and key way of doing fieldwork as well as delimiting the ethnographic field. Notions of lateral movement emerge as a counterpoint to immersion, embeddedness, integration and other such figurative expressions of downward passage into the field. More specifically, I discuss the metaphors of horizontal movement and thresholds that unfold on the scale of the city, the car and the unconscious. Thresholds, varying multifariously from gates to doors and checkpoints, feature prominently in this urban landscape, not only as literal and figurative gateways to the field but as outcomes of clashing political and epistemological processes.